Adiciones al conocimiento de Proscelidodon Bordas, 1935 (Mammalia, Xenarthra, Scelidotheriinae) - Miño Boilini, Ángel Ramón (2011)
The Scelidotheriinae subfamily constitutes a little diversified monophyletic group within the Mylodontidae, with a biochron that spans from the middle Miocene to the early Holocene. During the HuayquerianChapadmalalan age (late Miocene-middle Pliocene) the Scelidotheriinae are only represented by the genus Proscelidodon, being P. patrius the only species recognized for the Montehermosan stage/age (late Miocene-early Pliocene). Due to the scarcity of findings, the knowledge of the Neogene taxa included in this subfamily is limited, especially regarding the anatomical study of the postcranial skeleton. In this opportunity, the authors present the finding of a left hind limb partially complete in good condition of conservation, of an adult individual, assigned to Proscelidodon cf. P. patrius (Ameghino). The material was unearthed from the fluvial deposits of Monte Hermoso Formation (Buenos Aires, Argentina), in silty levels that represent flooding plain facies and that, biostratigraphically, correspond to Montehermosean stage/age. The detailed anatomical study of the different skeletal elements recovered, added to the comparison with other representative elements of this subfamily, provides novel data about the postcranial characteristics of Proscelidodon and allows us to evaluate its taxonomic and paleoecologic implications.